Elaboración de un plan de supervisión de agencias financieras mediante aplicación del ciclo de Deming, mejora continua - Mauricio Pérez, Irene Liliana (2017)
The formless present of labor experience in the company Mibanco, describes the case of the elaboration of a plan of supervision of financial agencies, by means of application of the cycle Deming, taking as source the reports that show the situation so much in the admission of credits and the administrative administration of the agencies, this as a result of the evaluation, pursuit and supervision, as well as the inspection in field, that which is the main activity that I carried out as Analyst of Admission of Credit Senior in the Area of Administration and Pursuit of Risks. The cycle Deming, is a basic and essential tool for the correct execution of continuous improvement in a company. This methodology describes the four main steps that should be carried out form systematically to achieve the continuous improvement, understanding as such to the continuous improvement of the quality. The evaluation considers variables of credit risk, which will be quantified obtaining a note that allows to qualify the situation of each agency, as a result the final result are summarized in Very Good, Good, to Regulate and Faulty. The tool allows to qualify to each agency by means of its advisers' of business individual evaluations (in the admission: clients' evaluation, presentation of credits and knowledge of normative, internal systems) and of the agency boss's administrative administration. He/she allows to know events that can cause credit risk. The main objective is to present the labor acting carried out in the company Mibanco like Analyst of Admission of Credit Senior in which I elaborated a plan of supervision of financial agencies with the purpose of improving the situation of each agency in which I acted. With the application of this plan it was possible to contribute with a tool supervision base for the financial agencies, being adapted to their objectives and their reality, corrigiendo and improving the administration in admission of credits and in the administration of the agency.